Synthesis and Evaluation of the Photocatalytic Activity of Nanostructured Composites Based on SiO2 Recovered by TiO2 - Werick Alves Machado; Higor de Oliveira Alves; Antonio Eduardo da Hora Machado (Orbital: The Electronic Journal of Chemistry, 2019)
Almost spherical SiO2 nanoparticles were recovered by thin films of TiO2 (highly crystalline anatase) produced in situ sol-gel syntheses. Silica coating was proven by scanning electron microscopy and infrared measurements. The outstanding photocatalytic efficiency of this material was proven by the degradation of the dye Ponceau 4R (P4R) in aqueous solution, by monitoring its discoloration as well as by the photocatalytic production of gaseous hydrogen. In the first case, the color of the solutions submitted to the photocatalytic process was reduced to zero in 140 minutes of reaction. Regarding the hydrogen production, 5.5 mmol of H2 were obtained in 5 hours of reaction, corresponding to a specific rate of production of 13.6 mmol g-1h-1, a value much higher than that obtained using TiO2 P25 (2.66 mmol g-1h-1) under similar conditions, or even with other photocatalysts reported in the literature. This outstanding photocatalytic activity is coherent with the specific surface area and porosity (respectively 70 m2/g and 15%), estimated for this material. On the other hand, this material presents noticeably superior band gap energy (Eg), 3.3 eV, when compared to the typical values found for TiO2. This small discrepancy, of 3%, may be the result of the mixture of electronic states of both materials.DOI: http://dx.doi.org/10.17807/orbital.v11i2.1347